Marketing Strategies Deploy By Malaysian Telecommunication Firms Specifically VOIP Sector - M., Linggeswary (2007)
This thesis deals with marketing strategy or strategies and marketing activities which deploy by Malaysian telecommunication industry specifically in marketing of VoIP product/service.